PLURALISME DAN TOLERANSI DALAM ISLAMIC WORLDVIEW: STUDI KEPUSTAKAAN HISTORIS-BUDAYA TENTANG PENDIDIKAN ISLAM DI PONDOK PESANTREN - Abdullah, Abdullah; Rohman, Abdul; Khafidoh, Khafidoh; Sumiran, Sumiran (STKIP Pesisir Selatan, 2025)
Pluralism and tolerance in Islamic education are often debated because they can be read as an affirmation of diversity and as a shared ethic that rejects violence. This article aims to explain how pluralism and tolerance are constructed within the pesantren Islamic worldview through historical–cultural trajectories, and to derive pedagogical implications. The study employs a historical–cultural library research design and thematic content analysis of relevant literature published in including journal articles, proceedings, and policy documents. The synthesis indicates that pesantren frame plurality as a social fact (sunnatullah) to be managed through maslahah-oriented reasoning, adab al-ikhtilaf, and ethical communication; tolerance is treated as an active moral competence cultivated through kitab learning, habituation of adab, kiai role modelling, deliberation (musyawarah), and social service (khidmah). Evidence from Javanese cultural da‘wah further shows that internalising tawhid can coexist with respect for local symbols, producing adaptive religiosity without theological relativism. The article’s novelty lies in mapping the pluralism–tolerance–moderation nexus across three layers of pesantren culture: the formal curriculum, dormitory-based hidden curriculum, and socio-historical tradition.